+0  
 
0
390
2
avatar
evaluate the expression.
(11 4) (5 2) (3 1)
 Feb 14, 2012
 #1
avatar
0
(a b) ----> a! / (b! * (a-b)! )

(11 4) ---> 11! / (4! * (7)! ) = 330

(5 2) ---> 5! / (2! * (3)! ) = 10

(3 1) ---> 3! / (1! * (2)! ) = 3
 Feb 14, 2012
 #2
avatar+3080 
0
tjloveley1:

evaluate the expression.
(11 4) (5 2) (3 1)



calc:

(a b) ----> a! / (b! * (a-b)! )


nice.

[input]ncr( 11, 4)[/input]
[input]ncr( 5, 2)[/input]
[input]ncr( 3, 1)[/input]
 Feb 14, 2012

33 Online Users

avatar
avatar
avatar
avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.